Relationship between Organizational Justice and Innovative Work Behaviours and Effects on Human Relation Practices Among the Hotels in Pakistan - Uzma, Ismail (2024)
The current study aimed to investigate the impact of organizational justice on the innovative work behavior of employees working in hotels in Pakistan, with a moderator of HRMPs. Previous literature highlighted the gaps relevant to organizational justice and its impact on employees' innovative work behavior in different sectors. The current study incorporated human resource management practices as a moderator to further strengthen the positive relationship between these two variables. The research depends on a 'quantitative philosophy' with 'purposive and convenience sampling.' The researcher tested organizational justice, innovative work behavior (IWB), and HRM practices using quantitative methods using SPSS version 25. Regression and multiple regression with maximum likelihood estimation were applied with a sample of 346 employees working in 52 hotels located in 9 cities: Lahore, Islamabad, Rawalpindi, Murree, Karachi, Faisalabad, Multan, Peshawar, and Sargodha of Pakistan, for testing hypotheses. The sample size calculation was done by using Kothari (2004). The results further explored the role of organizational justice and its direct and positive impact on employees' innovative work behavior. In addition, HRMPs directly and positively impact innovative work behavior. At the same time, they do not moderate the positive relationship between organizational justice and employees' innovative work behavior in these selected hotels in Pakistan. Key outcomes demonstrate that organizational justice impacts representatives' innovative work behaviour across all aspects. In particular, procedural and distributive justice affect IWB. HRMPs, including selection, training, compensation, performance appraisal, and participation, likewise decidedly influence IWB. In opposition to assumptions, HRMPs do not direct the connection between organizational justice and IWB. All things being equal, the study uncovers that pay is significant in moulding this relationship, recommending that fair and straightforward remuneration arrangements are fundamental for upgrading IWB in the lodging business. The study concludes that, in light of the preceding analysis and discussion regarding the influence of organizational justice on employee innovative work behavior in hotels in Pakistan, organizations must pay adequate attention to their human resources to improve employee innovative work behavior. The research emphasizes the importance of recognition and feedback in an employee's performance and how they impact employee work behavior in hotels. Furthermore, moderation analysis reveals that compensation plays a crucial role in shaping the relationship between organizational justice and innovative work behaviors. Therefore, employees' work behavior must be efficient by giving them compensation and benefits. Based on the foregoing results, it is suggested that management focus on strengthening the perception of justice in hotels to boost employees' work behavior. Organizational justice plays a significant role in improving employee work behavior within hotels. As a result, hotel management should develop and implement the finest organizational justice techniques to increase employee competency while meeting organizational goals. Furthermore, hotel management should ensure that the perception of justice for each staff member is clear, specific, and well-defined to ensure employee clarity and satisfaction in cases where they do not know how they are treated, which may fail to meet their set targets. Future research should investigate the qualitative application of organizational justice, innovative work behavior, and human resource management practice. Further, this relationship should consider other countries' mediation effects. This study contributes to theoretical advancements in understanding the dynamics of organizational justice and innovative work behaviors and offers practical implications for HR practitioners and policymakers within the hotel industry. The current study will ultimately benefit the top and middle management and policymakers by improving the perception of justice and innovative work behaviors of employees in hotels in Pakistan.